1998
DOI: 10.1074/jbc.273.28.17832
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Agrin in Renal Basement Membranes As Revealed by Domain-specific Antibodies

Abstract: We determined the specificity of two hamster monoclonal antibodies and a sheep polyclonal antiserum against heparan sulfate proteoglycan isolated from rat glomerular basement membrane. The antibodies were characterized by enzyme-linked immunosorbent assay on various basement membrane components and immunoprecipitation with heparan sulfate proteoglycan with or without heparitinase pre-treatment. These experiments showed that the antibodies specifically recognize approximately 150-, 105-, and 70-kDa core protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 50 publications
3
54
0
1
Order By: Relevance
“…1c). These results indicate that the decreased staining of the GBM by antiheparan sulphate antibody JM403 is not due to reduced synthesis of the core protein of agrin, which is the major heparan sulphate proteoglycan in the GBM [24,25]. In this analysis we also observed an inverse correlation between the heparan sulphate domain content of the GBM and the level of proteinuria (Fig.…”
Section: Resultssupporting
confidence: 66%
“…1c). These results indicate that the decreased staining of the GBM by antiheparan sulphate antibody JM403 is not due to reduced synthesis of the core protein of agrin, which is the major heparan sulphate proteoglycan in the GBM [24,25]. In this analysis we also observed an inverse correlation between the heparan sulphate domain content of the GBM and the level of proteinuria (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Most TBMs lacked staining for the C-terminus of agrin, whereas the N-terminus of agrin was present in most TBMs. 17 The difference in GBM staining pattern for N-and C-terminal agrin in the present study could be due to a reduced accessibility of the perimesangial GBM regions for the antibodies. This is, however, not very likely because the mAb against N-terminal agrin clearly stained both peripheral and perimesangial GBM parts.…”
Section: Discussionmentioning
confidence: 53%
“…54 Furthermore, agrin is a major heparan sulfate proteoglycan in the adult GBM. 17,55 The anionic heparan sulfate side chains of agrin play an important role in the maintenance of the charge-dependent permeability of the GBM. 56 -58 In the present study, we observed a difference in ultrastructural localization between the N-and C-terminus of agrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations